Motivation and self-efficacy as key factors influencing self-care in hypertensive adults: A cross-sectional study in Indonesia - Arif Setyo Upoyo; Yunita Sari; Eman Sutrisna; Agis Taufik; Hae-Ra Han (Faculty of Nursing Universitas Padjadjaran, 2025)
Introduction: Self-care is crucial for enhancing life quality and and preventing cardiovascular, renal, and vascular complications in individuals with hypertension. However, self-care among patient’s hypertension remains suboptimal. Our research aimed to identify the determinants of self-care practice among hypertensive patients in Indonesia. Methods: A survey that was cross-sectional. It carried out among 209 adults with hypertension attending community health centers in Central Java, Indonesia. Self-care behaviors, motivation, self-efficacy, and knowledge were assessed using the validated Hypertension Self-Care Profile (HBP-SCP) and Hypertension Knowledge-Level Scale (HKLS). Chi-square and multivariable logistic regression tests were used to evaluate the data. Results: Bivariate analysis revealed significant correlation between self-care behavior and motivation (p<0.001), self-efficacy (p<0.001), and history of hypertension in the family (p=0.018). No significant associations were observed for age, gender, education, occupation, body mass index, blood pressure, or knowledge (all p>0.05). Multivariable analysis demonstrated that motivation (OR=2.22, 95% CI=1.10–4.45, p=0.025) and self-efficacy (OR=7.84, 95% CI=3.99–15.39, p<0.001) were independent determinants of good self-care. Conclusions: Motivation and self-efficacy are key determinants of hypertension self-care behaviors among Indonesian adults. Interventions should prioritize strengthening motivation and building self-efficacy through motivational interviewing, skills training, and structured follow-up by nurses and other healthcare professionals.